Eco Spheres: Uma criação artística audiovisual no Antropoceno - Ana Isabel Carvalho dos Santos (2021)
In this research I intend to analyze how technology in audiovisual performative contexts can be an ally to (re)create necessary links to Nature and create an audiovisual performance for an open-air natural space. The concept of Ecosophy will serve as a theoretical anchor to support the theoretical and practical context. Cyclical mechanisms of Nature will be observed, documented and studied (e.g. night-day, sounds throughout the day, plant movement, tidal cyclicity, moon phases, ...) which will then inspire the practical and artistic work with audiovisual technology. The concept of "cyclical" will be worked artistically through audiovisual technologies, namely by the use of loops (i.e. repetition of a sound track) and visual repetitive gestures (i.e. repetition of a video track) in real time, thus creating an analogy with the cyclicality of Nature, with the ultimate goal of empathizing the audience for the Human-Nature reconnection.